Ethics education among obstetrics and gynecologists in Saudi Arabia: a cross-sectional study - Noha Abed Althagafi; Ghiath Alahmad (BMC Medical Education, 2023)
Abstract There are a lot of efforts to promote ethics education and training at an undergraduate and postgraduate level around the world, including in Saudi Arabia. However, there is still a lack of structured ethics education curricula in obstetrics and gynecology residency programs in Saudi Arabia. In the current scenario, where new ethical dilemmas are emerging, an ethics education that only focuses on teaching the ethical principles does not enhance the competence to deal with the ethical challenges in daily practice. This study evaluates the lack of ethics education and training in obstetrics and gynecology residency programs in Saudi Arabia. A cross-sectional survey of working obstetricians and gynecologists in Saudi Arabia was conducted among all working levels of doctors (the residents, registrars, consultants, and program directors) from various hospitals of Saudi Arabia. 391 practitioners responded to the survey, representing a response rate of 39.1%, including 257 (66.4%) females and 130 (33.6%) males. 74 (23.0%) received formal education (medical school = 35%; residency programs = 11.8%; sub-specialty programs = 4.3%; postgraduate programs = 7.4%), 85 (26.4%) received informal education (online training = 12.8%; conferences = 18.9%; courses and workshops = 13.3%; self-learning = 31.7% and daily practices = 20.7%), and 78 (19.95%) received no ethics education. Almost all the respondents had a positive attitude towards ethical principles, but a least percent were competent to deal with the ethical challenges. The bottom line of this survey is the imperativeness of reinforcement of formal ethics education in obstetrics and gynecology postgraduate programs in Saudi Arabia.